Ten Years On: CSR Motivations and Engagements in French Managers’ Perceptions 2007-2017 - Hudson, Sarah; Descubes, Irena (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
We investigate how managers in French companies report their engagements and motivations regarding corporate social responsibility (CSR) in 2007 and 2017. We conducted and analysed 14 in-depth structured interviews with managers in 2007 and again in 2017. Thematic analysis shows that in 2007, managers focused on instrumental motivations for CSR, citing economically driven artefacts and pro-environmental efforts. In 2017, most managers reported increased and reinforced environmental and social engagements with a parallel shift in the expression of their motivations; seeing CSR as a responsibility to society and future generations, or as a normal, natural activity.